Study The Turbidity Reduction by Using Ceramic Flat at Kampung Lama Orang Asli Leboh, Kangkar Senangar, Parit Sulong, Batu Pahat, Johor - Letchumanan, Sharmila; Tajul Baharuddin , Mohamad Faizal (Progress in Engineering Application and Technology, 2023)
Ceramic flats are used to treat underground water from tube wells in the Kampung Lama Orang Asli Leboh, Kangkar Senangar, Parit Sulong, Batu Pahat, Johor. Residents in this village have been facing the problem of getting a clean water supply for more than 50 years. Despite having a developed sand filtration system, but due to no effective maintenance system, the problem of clean water sources still cannot be solved. The water from the tube well was allied to the ceramic flat. Turbidity value was calculated before and after it was connected to the ceramic flat. The filtered water was tested for turbidity using a WTW 251210 pHotoFlex® Turb/SET Portable LED filter photometer. According to the drinking water quality standard in Malaysia, the maximum value that is permitted is 5 NTU. The flat value can be less than one NTU when using ceramic, meeting the study’s objective. Ceramic flats can reduce turbidity by 97%, according to this study. Ceramic flat can be used for daily water treatment and has a high rate of turbidity reduction. Ceramic flat can be used for daily water treatment and has a high rate of turbidity reduction.